IMPLEMENTASI KEKUATAN EKSEKUTORIAL TERHADAP HAK TANGGUNGAN DALAM RANGKA PENYELESAIAN KREDIT MACET BERDASARKAN AKTA YANG TELAH DIBUAT OLEH NOTARIS - Fadhilah Sundah; Jawade Hafidz (Jurnal Akta, 2017)
The mortgage right is one of the guarantee institutions in Indonesia that is often used in the provision of credit agreements whose arrangements are regulated in Law No. 4 of 1996 on Mortgage Rights. Against a non-performing loan, the mortgage holds stronger executorial strength compared to other guarantees in general. Registration of mortgages can only be done by the Land Acquisition Authority (PPAT) who has the authority as mandated by law with the establishment of a Deed of Assignment Rights (APHT) and registered by the relevant official to the National Land Agency (BPN) with the terms and times that have been determined as well.The existence of a bad credit is also caused by the debtor who has bad faith in installing the credit and expected a self-know system to know the financial history of debtors to the bank more thoroughly in conducting credit analysis. Keywords: The power of ekskutorial, mortgage rights.